Analisis Studi Kelayakan Bisnis Jasa MUA Duwi Samawa Wedding di Kabupaten Pemalang - Robiah, Siti; Abadi, Muhammad Taufiq (CV. Kalimasada Group, 2023)
Spending life and growing old with the ideal lover can be said to be a dream for everyone. Many people struggle to be able to build a legal relationship through a marriage. The implementation of a wedding reception is one of the events that is expected to be carried out once in a lifetime. The selection of MUA services is important to carve out a sweet marriage with MUA who is reliable and has good quality. So that the marriage documentation becomes memorable to look back on when old age arrives. This study aims to analyze the feasibility of the MUA service business. The research method used is a qualitative approach. The location in the selection of MUA services coincided with the Duwi Samawa Wedding MUA Service inPemalang Regency. The research results show that the analysis of market, competitor and marketing mix aspects shows that the prospects for the MUA Duwi Samawa Wedding service business are very good and feasible, this can be seen from the interest in renting MUA services where during Eid al-Fitr they make up three times the contract and reception in one day. The price range for renting is quite friendly, starting from Rp. 8.0000.000,- to Rp. 30,000,000,-. With quality make-up and excellent service, it can be said that those interested in renting MUA services have great opportunities. Through digital marketing promotion media and electronic word of mouth to support the marketing mix and expand the market share network.